The Effect of Rhythmic Gymnastics on Kinesthetic Intelligence Among First Grade Students of SD Negeri 105273 Helvetia - Nainggolan, Tiovany Debora; Karo Karo, Alan Alfiansyah Putra; Azandi, Filli; Lubis, Ade Evriansyah (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2025)
This study aims to empirically examine the effect of rhythmic gymnastics on the development of kinesthetic intelligence among first-grade elementary school students. The research employed an experimental design to determine the influence of rhythmic gymnastics (independent variable) on students’ kinesthetic intelligence (dependent variable). The population consisted of all students of SD Negeri 105273 Helvetia, while the sample included 13 first-grade students for the 2022/2023 academic year. The treatment involved rhythmic gymnastics sessions designed to enhance students’ body coordination, agility, balance, and strength. Pre-test and post-test assessments were conducted to measure kinesthetic intelligence. The average pre-test score was 12.30, while the post-test average increased to 23.15. Data were analyzed using the Wilcoxon and Mann-Whitney tests, showing a significance value (Asymp. Sig. 2-tailed) less than 0.05. The findings indicate a statistically significant effect of rhythmic gymnastics on the improvement of kinesthetic intelligence among students. The study concludes that rhythmic gymnastics can effectively enhance motor coordination, physical agility, and body control in early elementary students. This supports Gardner’s theory of multiple intelligences, emphasizing the role of movement-based learning in optimizing children’s physical and cognitive development.